A new species of Rhopalopsole Klapálek, 1912 with preliminary female identifications in this genus - Yang, Yu-Ben; Du, Yu-Zhou; Zhu, Bin-Qing (Zootaxa, 2022)
Although some females of Plecoptera are described in taxonomic literature, they are difficult to morphologically distinguish among regional congeners, and identifications are often made through inference only. Therefore, females of many species are unknown and it is often difficult to match males and females correctly. Recently, we reviewed the specimens of the genus Rhopalopsole Klapálek, 1912 that we collected and found that differentiation between female subgenital plates is significant and very helpful for the identification of species. A new species of this genus from Sichuan Province, Rhopalopsole singiplatta Yang & Du, sp. nov., is established based on morphological and molecular data. In addition, we used modern tree- and genetic distance-based phylogenetic methods to positively associate females with males for six species in total.